Applying Multivariate Analysis to Developing Electrodialytic Remediation of Harbour Sediments from Arctic Locations - Pedersen, Kristine Bondo (UiT Norges arktiske universitet, 2015)
This thesis consists of the following papers: PAPER I: Pedersen, K. B., Lejon, T., Jensen, P. E. & Ottosen, L. M. «Chemometric analysis for pollution source assessment of harbour sediments in Arctic locations”. (Manuscript). Published version available in Water, Air, & Soil Pollution 2015, 226:150. PAPER II: Pedersen, K. B., Kirkelund, G. M., Ottosen, L. M., Jensen, P. E. & Lejon, T. (2015). Multivariate methods for evaluating the efficiency of electrodialytic removal of heavy metals from polluted harbour sediments. Available in Journal of Hazardous Materials. 283. 712-720. PAPER III: Pedersen, K. B., Lejon, T., Jensen, P. E. & Ottosen, L. M. Screening of Variable Importance for Optimsing Electrodialytic Remediation of Heavy Metals from Polluted Harbour Sediments. (Manuscript). Accepted manuscript version available in Munin at https://munin.uit.no/handle/10037/8974 . Published version available in Environmental Technology 2015, 36(18). . PAPER IV: Pedersen, K. B., Ottosen, L. M., Jensen, P. E. & Lejon, T. : Comparison of 2-compartment, 3-compartment and stack designs for electrodialytic removal of heavy metals from harbour sediments. Manuscript). Accepted manuscript version available in Munin at http://hdl.handle.net/10037/8705 . Published version available in Electrochimica Acta 2015. 181: 48-57. PAPER V: Pedersen, K. B., Jensen, P. E., Ottosen, L. M. & Lejon, T.: Optimisation of 2-compartment cell for electrodialytic removal of heavy metals. (Manuscript). Published version with title “An optimised method for electrodialytic removal of heavy metals from harbour sediments” available in Electrochimica Acta 2015, 173: 432-439. PAPER VI: Pedersen, K. B., Lejon, T., Jensen, P. E. &, Ottosen, L. M.: Applying multivariate analysis as decision tool for evaluating sediment-specific remediation strategies. (Manuscript). Published version available in Chemosphere 2016, 151: 59-67. PAPER VII: Pedersen, K. B., Lejon, T., Jensen, P. E. &, Ottosen, L. M.: Influence of temperature on the ...